Proposing a level of maturity in strategic sourcing: A case study and survey in Brazil - Thiago Konrath; Fabiano Nunes; Cristine H. Nodari; Ana Lucia Miranda (Management Science Letters)
The objective of this study is to propose an instrument for identifying the level of maturity of purchasing and supply management in relation to Strategic Sourcing. Based on an initial model, a maturity measurement instrument was applied to a case study company in a chemical industry company in Vale dos Sinos, in order to validate the tool. Based on this, a survey was carried out with the aim of capturing the perception of purchasing professionals on the topic. By sending a questionnaire to 250 professionals in the purchasing and supply management area, a return rate of 28% (70 respondents) was obtained from this sample. For the data obtained, structural equation modeling (SEM) was carried out using Smart PLS 3.0® software. With the modeling, a load of 0.428 was obtained for the suppliers construct, 0.555 for the inventory construct and 0.158 for the indicators construct. Overall, the satisfactory constructs for this sample positively impact 67.8% on the Strategic Sourcing construct. Therefore, for this specific sample, the constructs referring to suppliers, inventory and indicators jointly impact Strategic Sourcing. The research in question proposed a model for a better understanding of Strategic Sourcing structures and aims to contribute to practical and organizational contexts regarding the maturity of this topic among purchasing professionals. This understanding aims to provide readers with greater empirical and academic understanding of this emerging and important topic for business and company competitiveness.